Developing implant dentistry education in Europe: the continuum from undergraduate to postgraduate education and continuing professional development. (March 2014) - Mattheos, N.; de Bruyn, H.; Hultin, M.; Jepsen, S.; Klinge, B.; Koole, S.; Sanz, M.; Ucer, C.; Lang, N. P.
Abstract: Introduction: Implant dentistry is a treatment modality which has mainstream clinical practice of comprehensive care, which however is not adequately represented in the undergraduate dental curricula. A consensus workshop organised by ADEE in 2008, set the benchmarks for the knowledge and competences a modern dental practitioner must possess with regard to implant dentistry, as well as defined undergraduate and postgraduate pathways for the acquisition of these competences. Today, 5 years later, there exist several challenges for the implementation of these benchmarks in both undergraduate curricula but also post‐graduation educational pathways. Methods: A consensus workshop was organised by ADEE, bringing together 48 opinion leaders, including academic teachers of all disciplines related to implant dentistry, specialists, representatives of relevant scientific and professional associations, as well as industry delegates. The objectives of the workshop were to evaluate the existing scientific literature, reported experience and best practices in order to identify potential and limitations for the implementation of implant dentistry in the undergraduate curriculum, as well produce recommendations for the optimal educational structures for postgraduate programmes and continuing professional development. Results: The scientific committee conducted two European‐wide questionnaire surveys to better document the current state of education in implant dentistry. Upon completion of the surveys, reviewers were appointed to produce three scientific review papers, identifying current achievements and future challenges. Finally, during the 3 days of the workshop, all the evidence was reviewed and the main conclusions and recommendations that were adopted by all participants are reported in the present Consensus Paper. Conclusions: Implementation of implant dentistry in the undergraduate curriculum has improved significantly, but still lags behind the benchmarks set in 2008 and the diversity between institutions remains big. At the post‐graduation level, there is currently a wide diversity of courses and pathways towards competences related to implant dentistry and there is at present a great need for quality assurance, as well as standardisation and transparency of the learning outcomes.